2020
DOI: 10.12688/f1000research.25923.1
|View full text |Cite
|
Sign up to set email alerts
|

All the right moves: why in utero transfer is both important for the baby and difficult to achieve and new strategies for change

Abstract: The best way to ensure that preterm infants benefit from relevant neonatal expertise as soon as they are born is to transfer the mother and baby to an appropriately specialised neonatal facility before birth (“in utero”). This review explores the evidence surrounding the importance of being born in the right unit, the advantages of in utero transfers compared to ex utero transfers, and how to accurately assess which women are at most risk of delivering early and the challenges of in utero transfers. Accurate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Also, no original study was found that compared the two groups. However, a study based on the case reports in the United Kingdom report that referral and dispatching of pregnant women to more well-equipped centres imposes additional psychological stress on them (Musson & Harrison, 2016;Watson et al, 2020). This report does not appear to be consistent with the results of our study.…”
Section: <001contrasting
confidence: 99%
“…Also, no original study was found that compared the two groups. However, a study based on the case reports in the United Kingdom report that referral and dispatching of pregnant women to more well-equipped centres imposes additional psychological stress on them (Musson & Harrison, 2016;Watson et al, 2020). This report does not appear to be consistent with the results of our study.…”
Section: <001contrasting
confidence: 99%
“…Threatened preterm labor (TPL) is one of the pregnancy complications that frequently leads to hospitalization of pregnant women (Bendix et al, 2016) or their referral to tertiary healthcare centers (Watson et al, 2020). In recent years, the survival rate of premature neonates has increased by using antenatal interventions such as administration corticosteroids and in utero transfer (Synnes et al, 2017; Watson et al, 2020). However, transferring women with TPL to the tertiary health care unit is costly and time-consuming and imposes considerable stress burden to the women and their families (Watson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the survival rate of premature neonates has increased by using antenatal interventions such as administration corticosteroids and in utero transfer (Synnes et al, 2017; Watson et al, 2020). However, transferring women with TPL to the tertiary health care unit is costly and time-consuming and imposes considerable stress burden to the women and their families (Watson et al, 2020). Considering that, not every hospitalized and transferred woman goes into preterm birth (Carter et al, 2018; Vivanti et al, 2019), it is essential to conduct a precise clinical assessment in order to prevent unnecessary referrals and interventions (Boland et al, 2017; Carter et al, 2018; Dabi et al, 2017; Vivanti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] They tend to decrease the intracellular calcium ion availability through various mechanisms, causing inhibition of interaction between actin and myosin. [ 8 9 ]…”
Section: Introductionmentioning
confidence: 99%